(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: To investigate the reasonableness of using proton pump inhibitors (PPI) at 120 Military Hospital in Tien Giang province. Subjects and methods: Cross-sectional descriptive study on 4532 outpatient prescriptions of patients who were prescribed drugs by doctors from July 1st, 2020 to July 30th, 2020 at clinics of the examination department - Military Hospital 120. Results: Prescribing unsafe proton pump inhibitors accounted for 12.13%. Percentage of prescriptions without instructions for use of proton pump inhibitors (0.79%). The proportion of prescription drugs with drug interactions was 52.14%, clopidogrel was the most interactive drug commonly used with PPIs (48.3%). The proportion of proton pump inhibitors indicated unreasonable was 9.76%. The proportion of prescriptions with proton pump inhibitors for gastritis treatment accounted for 66.14% of the total number of prescriptions with proton pump inhibitors that were not reasonable. Conclusion: The proportion of proton pump inhibitors was not safe and reasonable and the proportion of prescription drugs with no instructions on how long to use proton pump inhibitors were low. The proportion of prescription interacting drugs accounted for a high proportion, clopidogrel was the most interactive drug commonly used with PPIs. Unreasonable prescriptions in PPI used mainly gastritis.